Evaluating the economic viability and technological feasibility of a new SOFC-integrated energy system using CO2 capture unit - Sabbaghi, Mohammad Ali; Genceli, Hadi; Baniasadi, Ehsan (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
To decrease carbon emissions in energy production systems, a new system has been introduced and investigated that utilizes solid oxide fuel cells (SOFC), a closed Bryton cycle (CBC), and a carbon dioxide capture unit (CCU). An extensive mathematical model has been created to evaluate the thermodynamic efficiency of this combined system. Findings show that the exergy efficiencies of the separate components, including SOFC and SOFC-CBC, are 39% and 79%, respectively, and the integrated system exhibits a total cost rate of 109.3 $/hr. The system is equipped with a CO2 capture unit, allowing it to efficiently separate the carbon dioxide produced during combustion and store it in a designated tank. The system is designed to effectively absorb 90% of carbon dioxide, successfully separating an impressive 221.94 kg/h. The exergy analysis of the system reveals that the afterburner has the greatest exergy destruction. Therefore, this component has the potential for system improvement from a thermodynamic perspective. Furthermore, a comprehensive study on the influence of the system's key parameters has been conducted to understand the system's performance. Maximum efficiency is realized when the SOFC functions at a temperature of 600 K with a fuel utilization ratio of 3.7.
Keywords: Solid oxide fuel cell; Closed Bryton cycle; Techno-economic assessment; Efficiency; CO2 capture; OXIDE FUEL-CELL; GAS-TURBINE; POWER; EXERGY; CYCLE; PERFORMANCE; Chemistry; Electrochemistry; Energy & Fuels